CONTSID: a Matlab toolbox for standard and advanced identification of black-box continuous-time models. Issue 15 (2018) - Garnier, H.; Gilson, M.
Abstract: The CONtinuous-Time System IDentification (CONTSID) toolbox provides Matlab functions for estimating continuous-time black-box models of dynamical systems from measured data without having to fully characterize the mathematics governing the system behavior. The toolbox includes tools for standard identification of linear continuous-time models such as simple process, transfer functions and state-space models. The toolbox also provides algorithms for more advanced identification such as errors-in-variable (EIV) and closed-loop model estimation or to capture nonlinear system dynamics. This paper presents an overview of the main features of the latest release of the CONTSID toolbox and outlines some recent developments for on-line parameter and time-delay system estimation.